A strategy of making waste profitable: Nitrogen doped cigarette butt derived carbon for high performance supercapacitors. (15th December 2019) - Meng, Qi; Chen, Wenjiao; Wu, Linzhen; Lei, Jiehong; Liu, Xiaonan; Zhu, Wenkun; Duan, Tao
Abstract: With the consumption of nonrenewable energy, environmental and energy issues require prompt solutions. With cellulose acetate being the main component, cigarette butts have become one of the most common items of household garbage due to nondegradability, which poses an important challenge in dealing with a series of problems caused by the discarded cigarette butts. Based on this problem, this work prepares nitrogen-doped cigarette butt-derived carbon (N-CBDC) through continuous carbonization, activation and a subsequent hydrothermal method and applies it to supercapacitor electrode materials. N-CBDC has high specific surface area (1633.37 m 2  g −1 ), a hierarchical porous structure, oxygen-rich functional groups, and high contents of nitrogen doping. The results demonstrate that such nitrogen-doped cigarette butt-derived carbon applied has excellent specific capacitance (330.1 F g −1 at 0.5 A g −1 ), good rate performance (45.75% from 0.5 to 10 A g −1 ) and high cycling stability (93.48% after 10, 000 cycles). This strategy, along with thoroughly disposing of cigarette butt wastes and avoiding cigarette butt pollution to the environment, is also expected to be used to develop various carbon-derived materials for supercapacitors to tackle the problem of nonrenewable energy consumption. Highlights: Nitrogen doped cigarette butt derived carbon (N-CBDC) was successfully prepared and applied to supercapacitors. The characteristics of N-CBDC and its influence on the specific capacitance are described. N-CBDC has good specific capacitance and excellent cycle stability.